Sequence polymorphisms in the D-loop region of mitochondrial DNA and outcome of non-Hodgkin lymphoma. (10th September 2013) - Diao, Lanping; Wei, Guangchuan; Su, Huiling; Li, Huan; Song, Jiaojie; Gao, Yuhuan; Guo, Zhanjun
Abstract: Accumulation of single nucleotide polymorphisms (SNPs) in the displacement loop (D-loop) of mitochondrial DNA (mtDNA) might be associated with cancer risk and disease outcome. We have identified 140 SNPs including 26 SNPs with frequency distribution of minor allele greater than 5% in a case–control study for non-Hodgkin lymphoma patients previously. In this study, we assessed the predictive power of D-loop SNPs in NHL patients. Five SNP sites were identified by log-rank test for statistically significant prediction of NHL survival in a univariate analysis. In an overall multivariate analysis, allele 16304 was identified as an independent predictor of NHL outcome. The survival time of NHL patients with 16304C was significantly shorter than that of patients with 16304T (relative risk, 0.513; 95% CI, 0.266–0.989; p  = 0.046). The analysis of genetic polymorphisms in the mitochondrial D-loop can help identify subgroups of patients who are at a high risk of a poor disease outcome.